His Hiding Place is Darkness: A Hindu-Catholic Theopoetics of Divine Absence, by Francis X. Clooney, SJ - Forsthoefel, Thomas A. (Religions of South Asia, 2015)
His Hiding Place is Darkness: A Hindu-Catholic Theopoetics of Divine Absence, by Francis X. Clooney, SJ. Stanford, CA: Stanford University Press, 2014. xvi + 187 pp. 85.00. ISBN 9780804776806 (hardback). 24.95. ISBN 978-0-8047-7681-3 (paperback).